Como o dress code organizacional esculpe o corpo da mulher - Dias, Alessandra dos Santos Libretti (2018)
We know how big is the universe of organizations and how many countless aspects within its many areas involves: accounting, investments, billing and payments, sales, purchasing and human relations. We live in a much more complex organizational environment than at the time of the development of Taylor and Fayol management theories. To meet all the demands that have been created over the years for this development, theories of organizations have incorporated knowledge from several other sciences, such as biology, psychology, sociology, among others. Therefore, several aspects that were previously not considered, began to be analyzed in organizations, such as the influence of the environment, people management, organizational culture and the identity and image of organizations, among many others. Within this last area, one of the aspects that - even implicitly - is striking, is the use of dress code as a tool of expression of the organizational identity values as well as the hierarchy and belonging, or not, the employee group. For each there is a dress code2, which expresses their values in the organizational identity, and it is up to each organization to impose, an implicit or explicit way, this to employees. The adequacy of them to this dress code enables the expression of their belonging to this organization, its organizational identity and position in the hierarchy. To understand the functions and objectives of the dress code, it is important to make a study of the history of clothing, especially women's, which allows us to understand the fashion and clothing as a visual language. Our clipping to the history of dress is part of capitalism in the West, when male attire, coming from the English bourgeoisie, was accepted as the standard for the corporate environment for both men and woman. This costume which parts and practices liberated the movements of the body began to express the values of bourgeois society, discretion and sobriety through dark and neutral colors. The female body, prevented by moral and having underestimated his intelligence, held the woman in corselets and in their homes, as a trophy representing success and virility of her husband. In the course of history, to enter this appearance environment "distinct", women have adopted male attire symbols such as blazers, shirts, shoulder pads and even ties, in the most possible sober colors, seeking to express the same masculine values present in the corporate environment. Our research analyzes this language in the corporate environment through female dress code, as a manifestation of organizational culture, support of individual and collective identity of the bodies in the work environment, represented in films of the last four decades. The considerations here guide the objective of this work: conduct a study that articulates political theory and anthropology, fashion and management, with the method the visual ethnography to understand how the corporate dress code, imposed or suggested, sculpts the female body in organizations, as well as, how it interacts with the identity of the organization, establishing a relationship which influences the question of power and hierarchy. These perspectives are grounded in theories in the field of management, sociology, and anthropology and illustrated in selected movie passages